2022
DOI: 10.2186/jpr.jpr_d_20_00197
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dimensions of laser-milled grid-like microslits on shear bond strength between porcelain or indirect composite resin and zirconia

Abstract: Purpose: Zirconia cores and frameworks are widely used in restorative dentistry. Although these structures are veneered with porcelain for esthetic reasons, the use of indirect composite resins (ICRs) is expected to increase in the future. The purpose of this study was to investigate the effects of microslits of different dimensions formed by Nd:YVO 4 laser machining on the bond strength between two types of zirconia (3 mol% yttria-partially stabilized zirconia (Y-TZP) and ceria-partially stabilized zirconia/a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Additionally, a ceramic primer cannot be used to form a covalent bond with the zirconia crystalline structure. Thus, the primary goal of continuous improvement in the clinical practice of prosthodontics and operative dentistry is determining how to treat the zirconia surface to modify its physical or chemical properties to improve the bond between zirconia and dental cement [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a ceramic primer cannot be used to form a covalent bond with the zirconia crystalline structure. Thus, the primary goal of continuous improvement in the clinical practice of prosthodontics and operative dentistry is determining how to treat the zirconia surface to modify its physical or chemical properties to improve the bond between zirconia and dental cement [ 13 , 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…This method is convenient and cost-effective and can effectively increase the wettability and roughness of the zirconia [ 24 , 25 ], thereby improving the bonding durability of zirconia restorations [ 22 , 23 , 26 ]. Some scientists have recently attempted using plasma [ 2 , 27 , 28 ], laser [ 3 , 15 , 17 ], and fusion sputtering [ 29 , 30 ] for surface treatment. These techniques improve the zirconia–resin bond strength, but require unique or expensive equipment, involve complicated operation processes, and are difficult to standardize and impractical for dental practices.…”
Section: Introductionmentioning
confidence: 99%
“…Of the 13 selected studies, yttria-stabilized tetragonal zirconia polycrystals (Y-TZP) were assessed by 9 studies [8,9,[26][27][28][29][30][31][32] although ceria-stabilized tetragonal zirconia polycrystals (Ce-TZP) were also assessed by one study [27]. The effects of laser irradiation on lithium disilicatereinforced glass ceramic were investigated by four studies [33][34][35][36].…”
Section: Resultsmentioning
confidence: 99%
“…The effects of laser irradiation on lithium disilicatereinforced glass ceramic were investigated by four studies [33][34][35][36]. The following types of laser were assessed by the selected studies: Er,Cr:YSGG [9,30], Er:YAG [33,34,36], Nd:YAG [34], CO 2 [8,32,35,], and Nd:YVO 4 [27]. The laser irradiation parameters varied among the studies as seen in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“… 26 Subsequently, multiple studies have confirmed that laser engraving can significantly increase the SBS of Zr to DBRs or ICRs by creating micro-slits prior to bonding, which increases the surface area. 27 , 28 , 29 , 30 , 31 Accordingly, it is believed that laser engraving could improve the surface characteristics of PEEK, enhance mechanical bonding, and ultimately increase the SBS. 26 , 27 , 28 , 29 , 30 , 31 This study aims to evaluate the impact of grid-like microslits created by laser engraving on PEEK's surface and compare it with other mechanical surface treatments for bonding PEEK to DBRs or ICRs.…”
Section: Introductionmentioning
confidence: 99%